Experimental price index for elderly consumers. - Amble, Nathan; Stewart, Ken (Monthly Labor Review, 1994)
The experimental consumer price index compiled by the Bureau of Labor Statistics for Americans 62 years of age and older rose somewhat faster than the BLS's other CPIs. The index for older Americans rose 28.7 percent between December 1987 and December 1993, slightly more than increases of 26.3 percent for the CPI for urban consumers and 25.5 percent for the CPI for urban wage earners and clerical workers. Expenditures for medical care accounted for most of the difference. The behavior of the experimental index for older Americans is analyzed, and tables show the CPI for older Americans between December 1982 and December 1993 and other data.